INTERBUDGETARY RELATIONS AND OPTIONS FOR SOLVING THE PROBLEMS OF BUDGET SUBSIDIES - I. V. Sugarova (Вестник университета)
A comprehensive study of various aspects of the functioning of the system of inter-budgetary relations related to the problem of subsidization of budgets, justified approaches to identifying the causes, factors and consequences of its manifestation in the modern national economy has been carried out. The determining factors of the manifestation of subsidization, generalized on the basis of structural and functional reasons have been considered. The study has made it possible to draw a number of conclusions. In particular, it has been argued that taking into account the imperfection of the institutional contour of inter-budgetary relations, there is an increase in regional budget differentiation. It has been pointed out, that the true reasons for the emergence of budget subsidies must be found in the imperfection of modern inter-budgetary relations, which are formed in the appropriate macroeconomic environment. It has been proved, that the lack of incentives for high-quality performance of their budget functions contributes to theloss of independence of the majority of regional budgets.